(Mis)use of 133Ba as a calibration surrogate for 131I in clinical activity calibrators. (March 2016) - Zimmerman, B.E.; Bergeron, D.E.
Abstract: Using NIST-calibrated solutions of 131 Ba and 131 I in the 5 mL NIST ampoule geometry, measurements were made in three NIST-maintained Capintec activity calibrators and the NIST Vinten 671 ionization chamber to evaluate the suitability of using 133 Ba as a calibration surrogate for 131 I. For the Capintec calibrators, the 133 Ba response was a factor of about 300% higher than that of the same amount of 131 I. For the Vinten 671, the Ba-133 response was about 7% higher than that of 131 I. These results demonstrate that 133 Ba is a poor surrogate for 131 I. New calibration factors for these radionuclides in the ampoule geometry for the Vinten 671 and Capintec activity calibrators were also determined. Highlights: Relative responses of 131 I and 133 Ba in activity calibrators were investigated. Activity calibrators from two manufacturers investigated using standardized solutions. Relative responses of 133 Ba: 131 I ranged from +7% to +300%. Results indicate that 133 Ba should not be used as a calibration surrogate for 131 I.